Sirtuins, Bioageing, and Cancer - D. McGuinness; D. H. McGuinness; J. A. McCaul; P. G. Shiels (Journal of Aging Research)
The Sirtuins are a family of orthologues of yeast Sir2 found in a wide range of organisms from bacteria to man. They display a high degree of conservation between species, in both sequence and function, indicative of their key biochemical roles. Sirtuins are heavily implicated in cell cycle, cell division, transcription regulation, and metabolism, which places the various family members at critical junctures in cellular metabolism. Typically, Sirtuins have been implicated in the preservation of genomic stability and in the prolongation of lifespan though many of their target interactions remain unknown. Sirtuins play key roles in tumourigenesis, as some have tumour-suppressor functions and others influence tumours through their control of the metabolic state of the cell. Their links to ageing have also highlighted involvement in various age-related and degenerative diseases. Here, we discuss the current understanding of the role of Sirtuins in age-related diseases while taking a closer look at their roles and functions in maintaining genomic stability and their influence on telomerase and telomere function.